Learning-dependent gene expression of CREB1 isoforms in the molluscan brain - Sadamoto, Hisayo; Kitahashi, Takashi; Fujito, Yutaka; Ito, Etsuro (Frontiers in Behavioral Neuroscience, 2010)
Cyclic AMP-responsive element binding protein1 (CREB1) has multiple functions in gene regulation. Various studies have reported that CREB1-dependent gene induction is necessary for memory formation and long-lasting behavioral changes in both vertebrates and invertebrates. In the present study, we characterized Lymnaea CREB1 (LymCREB1) mRNA isoforms of spliced variants in the central nervous system (CNS) of the pond snail Lymnaea stagnalis. Among these spliced variants, the three isoforms that code a whole LymCREB1 protein are considered to be the activators for gene regulation. The other four isoforms, which code truncated LymCREB1 proteins with no kinase inducible domain, are the repressors. For a better understanding of the possible roles of different LymCREB1 isoforms, the expression level of these isoform mRNAs was investigated by a real-time quantitative RT-PCR method. Further, we examined the changes in gene expression for all the isoforms in the CNS after conditioned taste aversion (CTA) learning or backward conditioning as a control. The results showed that CTA learning increased LymCREB1 gene expression, but it did not change the activator/repressor ratio. Our findings showed that the repressor isoforms, as well as the activator ones, are expressed in large amounts in the CNS, and the gene expression of CREB1 isoforms appeared to be specific for the given stimulus. This was the first quantitative analysis of the expression patterns of CREB1 isoforms at the mRNA level and their association with learning behavior.